2021
DOI: 10.1093/bjsopen/zrab080
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of histological organ involvement in retroperitoneal sarcoma

Abstract: Background The prognostic significance of histological organ involvement by retroperitoneal sarcoma subtype is unknown. The present study aimed to describe organ involvement across the subtypes, and the implications for survival. Methods Patients undergoing surgery for primary retroperitoneal sarcoma at the Queen Elizabeth Hospital, Birmingham from April 2005 to September 2018 were identified retrospectively. Histological org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…For example, E. Nizri et al reported that intraperitoneal invasion was associated with increased LR and decreased survival, and Tyler et al reported that histologic organ involvement was associated with shorter OS. [ 24 , 25 ]. No additional prognostic factors for RPS were identified in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, E. Nizri et al reported that intraperitoneal invasion was associated with increased LR and decreased survival, and Tyler et al reported that histologic organ involvement was associated with shorter OS. [ 24 , 25 ]. No additional prognostic factors for RPS were identified in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…HOI is frequently observed following surgery for retroperitoneal liposarcomas. HOI stratifies the prognostic risk of patients with retroperitoneal leiomyosarcomas [37], while ongoing debate questions this association in well differentiated (WDLPS) and de-differentiated liposarcoma (DDLPS). A recent study found that the degree of HOI is an independent predictive factor for OS and DFS (Table 2).…”
Section: How To Improve Further Prognostication Of All Sarcomas: Inte...mentioning
confidence: 99%
“…Several studies have investigated the frequency of microscopic infiltration in resected organs in an attempt to help guide surgical decision making [36,37]. These data are inherently biased in that only resected tissue is available for study and the level of pathologic assessment is not standardized.…”
Section: Surgical Approachmentioning
confidence: 99%